Cacti : biology and uses - Nobel, Park S. (University of California Press, 2002)
The Cactaceae family, with about sixteen hundred species, is cultivated worldwide for fruits, forage, fodder, and even as a vegetable. Cacti are recognized for their attractive flowers, special stem shapes, and ability to tolerate drought. Because of their efficient use of water and other adaptations, biological and agronomic interest in cacti has soared.